Health Education for Schoolchildren Using Digital Games - Permata, Ariesza Trijitno; Safitri, Niken Dwi; Cherkashyn, Andrii (CV. Edutechnium Indonesia, 2024)
Media education in the digital age should be aligned with technological progress. Efficient instructional resources should be engaging, pertinent, easily obtainable, and linked to students. Social media has improved performance by facilitating expedited, more exact, and more precise communication, hence enhancing total productivity. Music characteristics, modifications, and captivating enhancements have gained significant popularity on social media sites. Social media plays a vital role for students, enabling them to gather information while improving their analytical skills and nurturing their talents and creativity in their academic pursuits. This study aims to ascertain the possible uses of viral social media as teaching instruments. This study utilizes a bibliographic analysis methodology, which entails a comprehensive scrutiny and assessment of books, theses, and written materials directly pertinent to the research topic from 2013 to 2023. This study utilizes the data analysis techniques of reduction, presentation, and conclusion. Optimizing the utilization of viral social media in educational material can amplify engagement and increase the overall learning experience. However, social media does not inherently have a harmful impact. The entire results of this study are meticulously outlined in this paper.